Nanowarming of vitrified pancreatic islets as a cryopreservation technology for transplantation - Taisei Wakabayashi; Masahiro Kaneko; Tomoki Nakai; Masanobu Horie; Hiroyuki Fujimoto; Masazumi Takahashi; Shota Tanoue; Akira Ito (Wiley, 2023)
Abstract Biobanking of pancreatic islets for transplantation could solve the shortage of donors, and cryopreservation of vitrified islets is a possible approach. However, a technological barrier is rewarming of large volumes both uniformly and rapidly to prevent ice formation due to devitrification. Here, we describe successful recovery of islets from the vitrified state using a volumetric rewarming technology called "nanowarming," which is inductive heating of magnetic nanoparticles under an alternating magnetic field. Convective warming using a 37°C water bath as the gold standard for rewarming of vitrified samples resulted in a decrease in the viability of mouse islets in large volumes (>1 ml) owing to devitrification caused by slow warming. Nanowarming showed uniform and rapid rewarming of vitrified islets in large volumes. The viability of nanowarmed islets was significantly improved and islets transplanted into streptozotocin‐induced diabetic mice successfully lowered serum glucose. The results suggest that nanowarming will lead to a breakthrough in biobanking of islets for transplantation.